2021
DOI: 10.3389/fped.2021.626261
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Management of Patent Ductus Arteriosus in Preterm Infants—A Systematic Review and Meta-Analyses Assessing Differences in Outcome Measures Between Randomized Controlled Trials and Cohort Studies

Abstract: Objective: This study aims to evaluate outcome after conservative management (no pharmacological/surgical intervention other than fluid restriction, diuretics, or ventilator adjustments) compared with active (pharmacological and/or surgical) treatment for patent ductus arteriosus (PDA) in preterm infants and analyze differences in outcome between randomized controlled trials (RCTs) and cohort studies.Study Design: This is a systematic literature review using PubMed, EMBASE, and Cochrane library. RCTs and cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 37 publications
0
13
0
1
Order By: Relevance
“…However, several prior meta-analyses, 27 , 28 randomised clinical trials 9 , 10 , 11 and observational cohort studies 13 , 14 , 15 , 16 did not show improved outcomes with PDA treatment. There might be several reasons for the conflicting results.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, several prior meta-analyses, 27 , 28 randomised clinical trials 9 , 10 , 11 and observational cohort studies 13 , 14 , 15 , 16 did not show improved outcomes with PDA treatment. There might be several reasons for the conflicting results.…”
Section: Discussionmentioning
confidence: 89%
“…There might be several reasons for the conflicting results. First, most studies 10 , 13 , 14 , 15 , 16 , 27 , 28 enrolled a large proportion of more mature preterm infants (28–32 weeks), and these infants were more likely to have spontaneous ductal closure and experience less haemodynamic effects from PDA. 29 Pooling data across gestational ages may mask the potential effect of PDA treatment on outcomes for the most immature population.…”
Section: Discussionmentioning
confidence: 99%
“…Conservative management for PDA pertains to interventions including fluid restriction, diuretics, or ventilator adjustments [ 18 ]. Fluid restriction is commonly practiced in preterm infants with PDAs, particularly in the setting of enteral feedings due to the increased risk of necrotizing enterocolitis [ 19 ].…”
Section: Reviewmentioning
confidence: 99%
“…1,6 In light of these observations, more stringent BPD definitions based on a systematic assessment of the need for respiratory therapy using pulse oximetry became more widely used in more recent randomized clinical trials (RCTs) to improve the consistency of the diagnosis of BPD across neonatal units. [14][15][16][17] Two large RCTs 18,19 that were specifically designed to determine the effect of high-dose enteral DHA supplementation during the neonatal period on BPD outcomes in preterm infants who were born before 29 weeks' gestation used such a systematic physiological BPD definition at 36 weeks' PMA. Contrary to the aforementioned hypothesis, both trials reported an overall increase of BPD with the use of DHA but an inconsistent association with BPD-free survival in analysis by gestational age (GA) and mode of delivery.…”
Section: Introductionmentioning
confidence: 99%